Genomics of high molecular weight plasmids isolated from an on-farm biopurification system - Martini, María C (2016)
Fil: Martini, María C. Consejo Nacional de Investigaciones Científicas y Técnicas de Argentina. Instituto de Biotecnología y Biología Molecular; Argentina.